The Characteristics Of The Dourados/Ms And Surrounding From The Series From 1980 To 2009 - Heverton Schneider; Charlei Aparecido da Silva (Geografares, 2014)
The study of climatic characteristics is presented as a fact of great importance, occupying a central position in the broad field of environmental science, with emphasis on studies of Climatology. For the development of this article, we attempted to discuss some variables such as climate (temperature, precipitation, relative humidity) for best explain and consolidate the theme, with the possibility that, variabilities were identified during the time series, especially in the last decade, a period considered from the 2000s. Meanwhile the paper discusses the climatic characteristics of the historical series focusing on the discussion of variability and possible climate trends for the city of Dourados/ MS and region.